ADMINISTRATION IN THE FIELD OF ECONOMIC RESPONSIBILITY (THEORETICAL ASPECT) - Матвійчук, Анатолій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: the article deals with the fundamental problem of economic responsibility from the standpoint of administrative law. The views of prominent scholars in the field of economic and administrative law in the category of economic responsibility are analyzed. Legal features of economic responsibility are provided. The principles of economic responsibility are formed. Proceeding from the above mentioned positions, the general concept of administration in the sphere of economic responsibility is proposed. Methods of research: the methodological basis of the study were general scientific methods of cognition. Results: the law may establish limits of economic and legal responsibility (which is aimed at protecting the property interests of participants in economic legal relations) or vice versa - the size of sanctions imposed by law is not directly related to the amount of damages (damage) caused by the unlawful conduct of a participant in economic relations (due to the need for protection public interest in the event that it is impossible to determine the specific size of the damage caused or the consequences of unlawful conduct may occur in the future). Based on the foregoing it is necessary to determine that the general concept of administration in the area of economic responsibility is in the area of administrative responsibility of legal entities. Establishment and standardization of this category will simplify the procedure for collecting funds from the state budget in case of violation of the requirements of economic, civil, administrative and environmental legislation by a legal entity. The system of theory, practice and principles of economic responsibility will help to develop the concept of administering economic responsibility. In legal literature, the notion of economic legal liability is investigated from a different angle, which leads to ambiguous attitude to the economic and legal responsibility of scientists and practitioners. Discussion: the general concept of the administration of economic responsibility is defined as the establishment of principles, functions and methods of scientific provision of economic responsibility from the standpoint of the rules of administrative law.